Pengaruh Sistem Informasi Manajemen Pengembangan Keprofesian Berkelanjutan dan Disiplin Kerja Terhadap Kompetensi Pedagogik Guru SMA Negeri di Kecamatan Kota Masohi - Jamair, Raddy; Wenno, I.H.; Rumfot, Sumarni (LP. Ma'arif Janggan Magetan, 2024)
In the teaching and learning process, a disciplined attitude is needed from a teacher so that learning objectives can be achieved. Professional development for teachers, in principle, must start from the teachers themselves. The Continuous Professional Development Management Information System is a program service of the Ministry of Education and Culture in an effort to improve teacher competencies, including pedagogical competencies. This research aims to (1) Describe the management information system for sustainable professional development of State High School teachers in Masohi City District. (2) Describe the work discipline of State High School teachers in Masohi City District. (3) Describe the pedagogical competence of State High School teachers in Masohi City District. (4) Describe the significant influence of the continuous professional development management information system on the pedagogical competence of State High School teachers in Masohi City District. (5) Describe the significant influence of work discipline on the pedagogical competence of State High School teachers in Masohi City District. (6) Describe the significant influence of the management information system for sustainable professional development and work discipline together on the pedagogical competence of State High School teachers in Masohi City District. This type of research is quantitative research. The samples obtained came from SMA Negeri 4 Central Maluku, SMA Negeri 15 Central Maluku and SMA Negeri 37 Central Maluku. The sample used was 106 respondents. The data in this research was obtained by filling out a questionnaire. The data analysis method used in this research is regression analysis. The results of descriptive analysis show that the category is very high on the variable management information system for continuing professional development of 76.42%, work discipline of 86.79% and pedagogical competence of 80.19%. Based on the results of testing the first hypothesis, it shows that the management information system for continuing professional development has a positive and significant effect on teacher pedagogical competence. The equation Ŷ=a + b1X1 = 95.317 + 0.567X1 is obtained, which means that every increase in the management information system variable of continuous professional development (X1) by one unit, the pedagogical competence variable (Y) will increase by 0.567 units with a constant value of 95.317. Furthermore, in testing the second hypothesis obtained a probability value of 0.000 <0.05, it is concluded that work discipline affects the pedagogical competence of public high school teachers in the Masohi City sub-district. Then, in testing the third hypothesis obtained a probability value of 0.000 <0.05, it is concluded that the management information system for sustainable professional development and work discipline affect the pedagogical competence of public high school teachers in Masohi City District. This means, the better the management information system for continuing professional development and work discipline, the better the pedagogical competence of public high school teachers in Masohi City District. Thus, it can be concluded that the management information system for continuing professional development and work discipline jointly affect the pedagogical competence of high school teachers in Masohi City District. Therefore, it is expected that related parties should review efforts to improve pedagogical competence in schools so that educational goals can be achieved optimally.